Problematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a ModeratorProblematic Social Media Use and Cyberbullying Perpetration in Unemployed University Students: Depression and Narcissistic Traits as Mediators and Social Connectedness as a Moderator (Journal of Asian Development Studies, 2025)
The aim of this study was not only to examine the relationship of problematic social media use with depression, narcissistic traits, social connectedness, and cyberbullying perpetration, but also to assess the mediating roles of depression and narcissistic traits, as well as the moderating role of social connectedness, between the predictor variable (problematic social media use) and the outcome variable (cyberbullying perpetration). The study employed a cross sectional correlational design and a purposive sampling technique to collect data from 139 unemployed university students from Pakistan and Turkey, aged at least 18 years, including both genders. The following instruments were used: the Bergen Social Media Addiction Scale (BSMAS), the Narcissism Short Form 16-Item Scale (to measure narcissistic traits), the Beck Depression Inventory-II (BDI-II), the Perpetration Subscale of the Cyberbullying Perpetration and Victimization Questionnaire (to measure cyberbullying perpetration), and the Social Connectedness Scale–Revised (SCS-R). The results revealed that problematic social media use was significantly and positively associated with depression, narcissistic traits, and cyberbullying perpetration, while it was negatively—but not significantly—associated with social connectedness. Hayes Process 4.2, Model 4, indicated that narcissistic traits, but not depression, significantly mediated the relationship between problematic social media use and cyberbullying perpetration.